Unpacking drivers of online censorship endorsement: Psychological and demographic factors - Houman Jafari; Hamid Keshavarz; Mahmood Khosrowjerdi; Dorota Rak; Alireza Noruzi (Computers in Human Behavior Reports)
This study explores the complex dynamics of online censorship endorsements within a national context. We examined the impact of some of the influential psychological and demographic factors contributing to online censorship endorsement of Iranian Telegram users. Through the analysis of 517 responses to an online questionnaire, we investigated the influence of variables such as age, education level, gender, the use of state-controlled media, political interests, personal trust, religiosity, perceived similarity, and motivated resistance to censorship on individuals' attitudes toward censorship. Our findings reveal that education level, state-controlled media usage, religiosity, perceived similarity, and motivated resistance to censorship significantly shape censorship endorsements in the Iranian Telegram users. The implications of these findings and avenues for further research are highlighted.